Sound-source localization as a multisystem process: The Wallach azimuth illusion - Yost, William A. (J Acoust Soc Am, 2019)
Wallach [J. Exp. Psychol. 27, 339–368 (1940)] described a “2-1” rotation scenario in which a sound source rotates on an azimuth circle around a rotating listener at twice the listener's rate of rotation. In this scenario, listeners often perceive an illusionary stationary sound source, even though the actual sound source is rotating. This Wallach Azimuth Illusion (WAI) was studied to explore Wallach's description of sound-source localization as a required interaction of binaural and head-position cues (i.e., sound-source localization is a multisystem process). The WAI requires front-back reversed sound-source localization. To extend and consolidate the current understanding of the WAI, listeners and sound sources were rotated over large distances and long time periods, which had not been done before. The data demonstrate a strong correlation between measures of the predicted WAI locations and front-back reversals (FBRs). When sounds are unlikely to elicit FBRs, sound sources are perceived veridically as rotating, but the results are listener dependent. Listeners' eyes were always open and there was little evidence under these conditions that changes in vestibular function affected the occurrence of the WAI. The results show that the WAI is a robust phenomenon that should be useful for further exploration of sound-source localization as a multisystem process.